FIRST-YEAR ENGLISH-MAJORED STUDENTS USE OF VIDEOS IN ENGLISH ON YOUTUBE AS EDUCATIONAL RESOURCES IN SELF-DIRECTED LISTENING SKILLS: PERCEPTION AND PRACTICE (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study investigates the first-year EFL students’ perception and the practice of the use of videos in English as educational resources in self-directed listening skills. 50 first-year students of English major, the University of Foreign Language Studies - University of Da Nang took part in the study. The data were collected from the questionnaire. The findings show a strong correlation between students’ perception and practice. Most first-year EFL students of UFLs have a positive perception of using YouTube videos in self-direct English listening skills and spend a quite large amount of time to practice.